2013
DOI: 10.5812/traumamon.11694
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Genitourinary Trauma in Southeastern Iran

Abstract: BackgroundTo survey genitourinary (GU) organ injury following general trauma, we performed an epidemiologic study of urogenital injuries in trauma patients referred to our hospital (a teaching hospital affiliated with the Zahedan University of Medical Sciences).ObjectivesWe aimed to assess the epidemiology of urogenital system injuries in southeastern Iran.Patients and MethodsFrom April 2009 to November 2011, all patients with GU injuries referred to our hospital were studied. The data including age, sex, type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…12 Other authors made similar findings. 5,6,10,13,14 However, this study showed that gunshot was the main mechanism of injury. 37.5% (n=39) of genitourinary injuries resulted from gunshots followed by motor vehicle collisions 26.9% (n=28).…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…12 Other authors made similar findings. 5,6,10,13,14 However, this study showed that gunshot was the main mechanism of injury. 37.5% (n=39) of genitourinary injuries resulted from gunshots followed by motor vehicle collisions 26.9% (n=28).…”
Section: Discussionmentioning
confidence: 89%
“…Sarvestani et al, in the assessment of genitourinary trauma in southeastern Iran had a mean age of 23±12 years while Barman et al, noted an average age of 27.45±14.2 years with highest incidence in the age group of 21 to 30 years. 6,7 There is a preponderance of males in trauma. 8 This is also reflected in injuries of the genitourinary system.…”
Section: Discussionmentioning
confidence: 99%
“…Of those, nine were excluded, with reasons. Finally, the remaining 40 articles [ 6 , 7 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 ], comprising a total of 2257 patients, were considered for our systematic review and meta-analysis. The main characteristics of the included studies are detailed in Table 2 .…”
Section: Resultsmentioning
confidence: 99%
“…There are several prognostic factors that can predict recovery or death from FG,[ 18 19 ] which include the results of NLR and PLR. [ 9 10 ] In our study, testing was carried out to assess the mortality compared to the prognostic factor.…”
Section: Discussionmentioning
confidence: 99%